Pigs’ Feed Fermentation Model with Antimicrobial Lactic Acid Bacteria Strains Combination by Changing Extruded Soya to Biomodified Local Feed Stock - Laurynas Vadopalas; Modestas Ruzauskas; Vita Lele; Vytaute Starkute; Paulina Zavistanaviciute; Egle Zokaityte; Vadims Bartkevics; Sarunas Badaras; Dovile Klupsaite; Erika Mozuriene; Agila Dauksiene; Sonata Sidlauskiene; et al. (Animals, 2020)
The aim of this study was to apply newly isolated antimicrobial characteristic possessing lactic acid bacteria (LAB) starters (Lactobacillus plantarum LUHS122, Lactobacillus casei LUHS210, Lactobacillus farraginis LUHS206, Pediococcus acidilactici LUHS29, L. plantarum LUHS135, and Lactobacillus uvarum LUHS245) for local stock (rapeseed meal) fermentation and to evaluate the influence of changing from an extruded soya to biomodified local stock in a feed recipe on piglets’ fecal microbiota, health parameters, growth performance, and ammonia emission. In addition, biomodified rapeseed meal characteristics (acidity and microbiological) were analyzed. The 36-day experiment was conducted using 25-day-old Large White/Norwegian Landrace (LW/NL) piglets, which were randomly distributed into two groups: a control group fed with basal diet and a treated group fed with fermented feed (500 g/kg of total feed). The study showed that the selected LAB starter combination can be recommended for rapeseed meal fermentation (viable LAB count in fermented feed 8.5 ± 0.1 log10 CFU/g and pH 3.94 ± 0.04). At the beginning of the in vivo experiment, the microbial profiles in both piglet groups were very similar: The highest prevalence was Prevotella (34.6–38.2%) and Lactobacillus (24.3–29.7%). However, changing from an extruded soya to fermented rapeseed meal in the feed recipe led to desirable changes in piglets’ fecal microbiota. There was a more than four-fold higher Lactobacillus count compared to the control group. Furthermore, there was significantly lower ammonia emission (20.6% reduction) in the treated group section. Finally, by changing from an extruded soya to cheaper rapeseed meal and applying the fermentation model with the selected LAB combination, it is possible to feed piglets without any undesirable changes in health and growth performance, as well as in a more sustainable manner.